1995: Hiroshima Memories: One sunny day, a young girl learned about darkness. (1st November 2020) - Friedman, Hideko Tamura
ABSTRACT: The Bulletin originally published "Hiroshima Memories" in its May/June 1995 issue. The author was a child in Hiroshima when the city was destroyed in 1945 by an atom bomb. She came to the United States in 1952, after finishing high school. The article is republished here as part of a special issue commemorating the 75 th year of the Bulletin .